Efektivitas Ekstrak Biji dan Buah Ginje (Thevetia peruviana) untuk Mencegah Kontaminasi pada Perkecambahan Biji Kacang Hijau Secara In Vitro - PUSPITOSARI, DIAN EKA; , Triastuti Rahayu, M.Si (2016)
Tissue culture is one of the techniques of plant propagation in aseptic conditions. Thevetia peruviana is a perennial dicotyledonous plants throughout the year are included in the family Apocynaceae that serves as an antibacterial, antifungal and anti-termite. The purpose of this study was to determine the effectivity of seeds and fruits extract of ginje (Thevetia peruviana) for prevent contamination in green beans seed germination in in vitro. Culture media using ½ MS media. Media culture planted by green beans. This research method using a completely randomized design (CRD) with two factors, factor 1 is varians extract, namely: seed and fruit ginje and factor 2 is concentration of extract, namely: 0% (K1), 15% (K2) and 30% (K3) . The extraction method of seeds and fruits ginje is using infundation. The results showed that in fruit thevetia extract bottle is more prevent contamination 40% and seed germination is normally, while in seed extract thevetia, the bottle which not contamination presentation is low and seed germination abnormal. The fruit thevetia extract in E2K2 and E2K3 concentration is more effective for prevent contamintation in green beans seed germnination in in vitro.